Instagram-Based Peer Counseling Effectiveness Students' Child Marriage Prevention Self-Efficacy - Sri Mulyani (Universitas PGRI Yogyakarta, 2026)
Child marriage is driven by poverty, lack of access to education, gender inequality, and cultural norms, and can be countered through self-efficacy and digital counseling. This study assesses the efficacy of Instagram-based peer counseling in improving students' self-efficacy versus conventional peer counseling, such as face-to-face. This quasi-experimental study used a pre-test-post-test design with 220 high school students in Bojonegoro, Indonesia. The intervention group received Instagram-based peer counseling, while the control group received conventional peer counseling. Self-efficacy was evaluated using validated instruments that evaluated three dimensions: generality, level, and strength. The data were analyzed using the Mann-Whitney U Test and the Wilcoxon Signed-Rank Test. Statistical results indicated significant improvements in both the experimental and control groups (Z = -8.836, p < 0.001 for the experimental group; Z = -8.819, p < 0.001 for the control group), with Instagram-based interventions showing superiority, supported by Mann-Whitney U results showing significant differences between groups (p < 0.001). Instagram-based peer counseling significantly enhances students' self-efficacy, particularly in the areas of generality, level, and strength. Schools should integrate Instagram-based peer counseling into reproductive health curricula. Keywords: child marriage prevention, digital peer counseling, instagram intervention, quasi-experimental study, self-efficacy